Chronic use of PAH-specific therapy in World Health Organization Group III Pulmonary Hypertension: a systematic review and meta-analysis. (March 2017) - Prins, Kurt W.; Duval, Sue; Markowitz, Jeremy; Pritzker, Marc; Thenappan, Thenappan
Pulmonary hypertension (PH) complicating chronic obstructive pulmonary disease (COPD-PH) and interstitial lung disease (ILD-PH) (World Health Organization [WHO] Group III PH) increases medical costs and reduces survival. Despite limited data, many clinicians are using pulmonary arterial hypertension (PAH)-specific therapy to treat WHO Group III PH patients. To further investigate the utility of PAH-specific therapy in WHO Group III PH, we performed a systematic review and meta-analysis. Relevant studies from January 2000 through May 2016 were identified in the MEDLINE, EMBASE, and COCHRANE electronic databases andwww.clinicaltrials.gov . Change in six-minute walk distance (6MWD) was estimated using random effects meta-analysis techniques. Five randomized controlled trials (RCTs) in COPD-PH (128 placebo or standard treatment and 129 PAH-medication treated patients), two RCTs in ILD-PH (23 placebo and 46 treated patients), and four single-arm clinical trials (50 patients) in ILD-PH were identified. Treatment in both COPD-PH and ILD-PH did not worsen hypoxemia. Symptomatic burden was not consistently reduced but there were trends for reduced pulmonary artery pressures and pulmonary vascular resistance with PAH-specific therapy. As compared to placebo, 6MWD was not significantly improved with PAH-specific therapy in the five COPD-PH RCTs (42.7 m; 95% confidence interval [CI], –1.0 – 86.3). In the four single-arm studies in ILD-PH patients, there was a significant improvement in 6MWD after PAH-specific treatment (46.2 m; 95% CI, 27.9–64.4), but in the two ILD-PH RCTs there was not an improvement (21.6 m; 95% CI, –17.8 – 61.0) in exercise capacity when compared to placebo. Due to the small numbers of patients evaluated and inconsistent beneficial effects, the utility of PAH-specific therapy in WHO Group III PH remains unproven. A future clinical trial that is appropriately powered is needed to definitively determine the efficacy of this widely implemented treatment approach.